Coordenação pedagógica: trabalho de articulação e encaminhamentos pedagógicos desenvolvidos em escolas municipais de Cascavel/PR - Carnaval, Geórgia Stéphanie Kieltika (2020)
The pedagogical coordination has marked its existence as an organ that promotes the articulation of educational actions in schools. Therefore, what is the repercussion of the routine practices of pedagogical meetings on the specificity of the Class Council, in the schools of Basic Education, for the professional consolidation as a teacher? How are the pedagogical works organized to deepen and analyze the situations, problems and difficulties mentioned in the dialogues and decisions made in the pedagogical meetings of the Class Council? These questions motivated the present study, which aims to unveil the institutional reality of pedagogical coordination, based on the perception of pedagogical meetings in their unfolding in the school routine, presenting discussions that value this space as the locus of teacher’s professional qualification with a view to improve school teaching practices and not to focus only on bureaucracies. We conducted the study in municipal schools in Cascavel/PR, with a sample of 30%, therefore, fifteen schools, contemplating the urban geographic regions of the city as a criterion of quantitative definition to compose the intended sample, there was a random draw to choose these schools. It is a qualitative research in the school environment, with a phenomenological approach, which revealed, through the analysis of the daily records in Class Council meetings, the actions and consequences of the decisions taken that may constitute proposals for continuing professional development for teachers. The research corpus was composed of Categories of Analysis which refer to the study objective, highlighted in the readings and analysis of the formal documents that presents the records of the Class Council meetings promoted by the pedagogical coordination of schools in the period of the year 2017. We seek to understand how the pedagogical coordination can contribute to the improvement of teacher practice, enabling a continuous qualification of their teaching practice and providing an opportunity for the debate to build/constitute a space for continuing education for teachers, based on the daily experiences of pedagogical meetings in schools We understand that the meaning units synthesized in Categories of Analysis, brought the essence of our research, presenting important aspects to understand this phenomenon, contributing to the role of the pedagogical coordinator and the continuing education for teachers in school.